2009
DOI: 10.1056/nejmoa0900429
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Vertebroplasty for Painful Osteoporotic Vertebral Fractures

Abstract: We found no beneficial effect of vertebroplasty as compared with a sham procedure in patients with painful osteoporotic vertebral fractures, at 1 week or at 1, 3, or 6 months after treatment. (Australian New Zealand Clinical Trials Registry number, ACTRN012605000079640.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
1,015
5
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,284 publications
(1,047 citation statements)
references
References 29 publications
11
1,015
5
16
Order By: Relevance
“…Traditionally, VP has been accepted as a successful procedure for treating VCFs; but three recently published RCTs comparing VP with a sham procedure [21,22] or NSM [20] have created contention about the efficacy of VP. Potential flaws confounding the outcomes have been previously outlined: these include low accrual rates at busy centers, inclusion of patients with subacute/chronic fractures, sham design, and no reported clinical examination to determine the source of pain [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, VP has been accepted as a successful procedure for treating VCFs; but three recently published RCTs comparing VP with a sham procedure [21,22] or NSM [20] have created contention about the efficacy of VP. Potential flaws confounding the outcomes have been previously outlined: these include low accrual rates at busy centers, inclusion of patients with subacute/chronic fractures, sham design, and no reported clinical examination to determine the source of pain [23].…”
Section: Discussionmentioning
confidence: 99%
“…There is class I evidence to support the superiority of vertebral augmentation procedures (VAPs) over NSM [8][9][10], as well as non-randomized prospective studies [11][12][13], systematic reviews [14][15][16][17][18][19], and numerous retrospective series supporting safety and effectiveness of these procedures. However, recently published randomized controlled trials (RCTs) that showed no superiority of VP over NSM [20] or over a simulated procedure (sham) [21,22] have raised questions regarding the value of VP. These trials have been criticized for potential methodological flaws confounding the outcomes [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the trial by Deviere and colleagues there were concerns that patients could have known the allocation because the copolymer used in the active arm had a distinct smell 55 . In trials on vertebroplasty, a container with cement was opened during placebo procedure to help with blinding 42, 56 .…”
Section: Strategies Used To Maintain Blinding In Interventional Placementioning
confidence: 99%
“…For example, the results of the vertebroplasty trials 42, 56 were criticised because the elements of placebo procedure could have had an effect on the reported pain, namely, a potential pharmacological anaesthesia due to injection of an anaesthetic into the facet capsule and periosteum 57 .…”
Section: Strategies Used To Maintain Blinding In Interventional Placementioning
confidence: 99%
See 1 more Smart Citation